Metode Hipnoterapi dalam Mengobati Trauma - Dwi Karina Ihsan (Gunung Djati Conference Series, 2023)
This study aims to discuss how hypnotherapy methods treat traumatic experiences experienced by victims. This study uses a qualitative approach by applying descriptive methods in its discussion. The formal object of this study is the hypnotherapy method while the material object is treating the trauma experienced by clients. The results in this study stated that hypnotherapy methods are also known to be effective in treating mental disorders such as trauma and stress. Usually the trauma experienced comes from unpleasant experiences or events so that it can be stored in the client's subconscious. Where if left for a long time and not treated as soon as possible it can have an impact on their sense of security and social interaction with the environment. This study concludes that through hypnotherapy methods that are directly related to the client's subconscious can be used as an alternative treatment to treat mental disorders.